Hubungan Peran Petugas Kesehatan Prolanis dengan Keaktifan Peserta Prolanis di UPTD Puskesmas Pujokerto Kecamatan Trimurjo Lampung Tengah Tahun 2024: The Relationship Between the Role of Prolanis Health Officers and the Participation Activeness of Prolanis Members at UPTD Pujokerto Health Center, Trimurjo Subdistrict, Central Lampung, in 2024 - Ria Melati; Wisnu Probo Wijayanto; Sutrisno; Rice Hernanda (MPI Press, 2024)
Introduction: In partnership with the Health Social Security Administering Body (BPJS), Primary Health Facilities or Community Health Centers administer the Chronic Disease Management Program (Prolanis), a preventive promotion program that includes health condition monitoring services, healthy living counseling, and Prolanis exercise activities. Prolanis implementation at the Pujokerto Public Health Center in 2023 has fallen short of the health center's goal; the activeness of Prolanis members is 46.83%, which is deemed low and falls short of the 75% target set by the health center. Prolanis health workers play a crucial role in operating the program by effectively managing and documenting the outcomes of the health examinations conducted, which helps Prolanis members understand the significance of preserving their health. Objectives: The research objective was to determine the correlation between the role of Prolanis health workers and the activeness of Prolanis participants at the Pujokerto Public Health Center. Method: The research type used is quantitative analytic and this research was conducted at the Pujokerto Public Health Center of Trimurjo Sub-District Central Lampung Regency. The population in this study was 252 people and the sampling was 72 people. Bivariate analysis using the Chi Square formula. Result: The results of the study indicate that the role of Prolanis health workers at the Pujokerto Health Center has been running well. The activeness of Prolanis participants at the Pujokerto UPTD was 61 people (84.72%). The relationship between the role of Prolanis health workers and the activeness of Prolanis participants at the Pujokerto Health Center, Trimurjo District, Central Lampung Regency in 2024. This is evidenced by the results of the p-value analysis = 0.000 which is smaller than α = 0.05 or 0.000 <0.05. Conclution: There is a significant correlation between the role of Prolanis health workers and the activeness of Prolanis participants at the Pujokerto Public Health Center of Trimurjo Sub-District Central Lampung in 2024.